The role of long noncoding RNA SNHG7 in human cancers (Review) - Bian, Zheng; Ji, Wei; Xu, Bing; Huang, Weiyi; Jiao, Jiantong; Shao, Junfei; Zhang, Xiaolu (Molecular and clinical oncology, 2020)
Long non-coding RNAs (lncRNAs) have been demonstrated to serve important roles in a variety of human tumor types. The lncRNA small nucleolar RNA host gene 7 (SNHG7) is associated with a variety of cancer types, such as esophageal cancer, breast cancer and gastric neoplasia. Based on previous studies that examined SNHG7 expression in tumors, it has become clear that SNHG7 modulates tumorigenesis and cancer progression by acting as a competing endogenous RNA. SNHG7 can sponge tumor-suppressive microRNAs and regulate downstream signaling pathways. In addition, overexpression of SNHG7 is associated with the clinical characteristics of patients with cancer by regulating cellular proliferation, invasion and metastasis and by inhibiting apoptosis via a variety of mechanisms of action. The function of SNHG7 in tumorigenesis and cancer progression indicates that it can potentially act as a novel therapeutic target or a diagnostic biomarker for cancer therapy or detection, respectively.